Inhibitory Effect of 6-shogaol on Fructose-Induced Protein Glycation and Oxidation in Vitro - Malakul, Wachirawadee; Pengnet, Sirinat (Asian Health, Science and Technology Reports, 2017)
Advanced glycation end product (AGEs), the final products derived from the non enzymatic modification of proteins by reducing sugars, plays an important role in the development of diabetic complications. Therefore, the inhibition of AGE formation may be an important therapeutic strategy to prevent the development of AGEs related diseases. The aim of this study was to investigate the in vitro effect of 6-shogaol on fructose-induced the formation of AGEs and protein oxidation. Antioxidant activity of 6-shogaol was determined by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. The protein glycation inhibitory potential was evaluated using in vitro BSA/ fructose model. 6-shogaol (0.1-10 mM) was incubated with BSA and fructose (0.1 M) at 37° C for 21 days. Antiglycation activity of 6-shogaol was investigated by measuring the formation of AGE-specific fluorescence and Nε-(carboxymethyl) lysine (CML). In addition glycation induced protein oxidation was examined using the protein carbonyl assays. 6-shogaol exhibited an effective antioxidant activity, Where the results that 6-shogaol inhibited the formation of both fluorescent AGEs and non-fluorescent AGE (CML) in BSA/fructose solution. In addition an increase in protein carbonyl content of BSA incubated with fructose was attenuated by 6-shogaol (10 mM). In conclusion, These results suggest that 6-shogaol has a inhibitory effect on the formation of AGEs and protein oxidation in vitro, which may be mediated through its antioxidant activity.